FAKTOR PENYEBAB KESULITAN BELAJAR BAHASA INGGRIS MAHASISWA STKIP PEMBANGUNAN INDONESIA - Khaerati Khaerati (Cross-border, 2021)
This resaerch aimed at finding out the factors which caused the students of STKIP PI had difficulties in learning English. This research applied qualitative method by adapting and applying coding method. This research also applied coding method in data analysis. Coding is a process of qualitative data dispalying in the forms of words, phrases, sentences which were classified as codes and labels. The data collected until saturated. Tha Data analysis includesd three stages; data reduction, data display, conclusion and verification. The subjects of the research were taken from 30 students of Biology Education Studi Program in Semester two Academic Year 2019-2020 and 30 students of Economics Education Studi Program in Semester eight Academic Year 2019-2020, STKIP Pembangunan Indonesia. The result of the this research showed that there were two general factors which caused the students of STKIP PI had difficulties in learning English. Internal factors which were from the students themselves that included the lack of motivation in learning English, laziness, lack of awareness on the benefits of English itslef. Mean while, the external factors are devided into two main factors; the first was dealing with the material of English subject like pronunciation, vocabulary mastery, words classification, reading ability, spelling, homonym as well as translating. While the second external factors were dealing with the lack of facilities and resourches which could support the learning process, lack of time and supporting athmosphere in practicing English. Based of the findings, it may concluded generally that there were internal and external factors which caused the students of STKIP PI had difficultties in learning English.